Characteristics of low-rank coal reservoir and exploration potential in Junggar Basin: new frontier of low-rank CBM exploration in China - Yuanjiang Yu; Yonghua Wang (Journal of Petroleum Exploration and Production Technology, 2020)
Abstract Low-rank coal reservoirs of Badaowan Formation and Xishanyao Formation are mainly developed in Junggar Basin. This paper discussed their features and coalbed methane (CBM) exploration potential based on geological survey, coal samples testing and mathematical fitting analysis. The pores are mainly small-micro- and large pores, and the porosity is 3.25–27.4% with an average of 9–10.51%; and macro-cracks and micro-fissures are well developed leading to a great variation of the permeability. The shallow coal reservoirs are mostly undersaturated, and the gas saturation tends to increase toward the deep coalbed. The J2x has a stronger methane adsorption and storage capacity than that of J1b and better physical properties, making CMB recovery easier. The coalbed reservoirs in middle-east of southern margin, eastern part and hinterland of Junggar Basin reach methane-rich to extremely methane-rich coalbeds and have strong ability to adsorb and store CBM. Coal seam gas shows generally, and the measured gas-bearing property is good. Low-rank CBM accounts for the majority of CBM resources in the basin. According to Langmuir volume, the gas provinces are classified into four types of blocks, i.e., CBM-poor (< 8 m3/t), CBM-bearing (8–15 m3/t), relatively CBM-rich (15–20 m3/t) and CBM-rich (> 20 m3/t). The relatively CBM-rich blocks cover block of well Qing 1 to Qi 8, Changji–Urumqi–Fukang area and slope belt of northwest margin to basin hinterland; while the CBM-rich blocks include most of eastern Junggar Basin. Since 2005, a series of special exploration and research of CBM have been carried out successively, and significant progress has been made in exploration of deep and shallow combination, conventional (gas) and unconventional (gas) combination. Recently shallow CBM exploration has achieved gas extraction at Dahuangshan coal mine, industrial gas flow wells in western Baiyanghe, and breakthrough of deep CBM exploration in Baijiahai area has been made, which confirmed the great development potential of low-rank CBM. The southern margin and the east of Junggar Basin have become the new frontier of low-rank CBM exploration in China.